2020
DOI: 10.1186/s12942-020-00217-1
|View full text |Cite
|
Sign up to set email alerts
|

A spatially explicit analysis of chronic diseases in small areas: a case study of diabetes in Santiago, Chile

Abstract: Background: There is a strong spatial correlation between demographics and chronic diseases in urban areas. Thus, most of the public policies aimed at improving prevention plans and optimizing the allocation of resources in health networks should be designed specifically for the socioeconomic reality of the population. One way to tackle this challenge is by exploring within a small geographical area the spatial patterns that link the sociodemographic attributes that characterize a community, its risk of suffer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Other health behaviours or conditions identified in the review included problem gambling [18], mental health and alcohol consumption [19] and combinations of health outcomes [20][21][22][23]. Dental health [24], diabetes [25] and mortality [26] are more recent topics that were modelled. Spatial microsimulation for resource allocation, with the example of maternity services in England [27], or estimating the impacts of policies on health [28] were more unusual applications of this method for public health interests.…”
Section: Search Resultsmentioning
confidence: 99%
“…Other health behaviours or conditions identified in the review included problem gambling [18], mental health and alcohol consumption [19] and combinations of health outcomes [20][21][22][23]. Dental health [24], diabetes [25] and mortality [26] are more recent topics that were modelled. Spatial microsimulation for resource allocation, with the example of maternity services in England [27], or estimating the impacts of policies on health [28] were more unusual applications of this method for public health interests.…”
Section: Search Resultsmentioning
confidence: 99%
“…Efforts in this direction have started by building remotely sensed socioeconomic maps in several countries combining multiple data sources like mobility, satellite, night-light emission, or online social media, but still much research is needed 49 52 . Both traditional statistical approaches such as Iterative Proportional Fitting, Monte Carlo sampling, and machine learning techniques such as Self-Organized Maps or Generative Adversarial networks are appropriate candidates to generate synthetic behavioral data from novel data sources 53 – 55 . The synthetic and inferred data could then be used to represent mobility or contact patterns of subpopulations that will feed epidemic models, in a similar way to what is customarily done for age-dependent contact matrices 56 , 57 .…”
Section: Computational and Digital Epidemiology Approaches To Address...mentioning
confidence: 99%
“…These initiatives have not changed the fact that inequality and privatization are still the hallmarks of the Chilean health care system ( Rotarou and Sakellariou, 2017a ). Offering an example of this, the study conducted by Crespo et al (2020) showed that there is a strong spatial correlation between demographics and chronic diseases in Chilean urban areas. High-income groups with high educational levels had a significantly lower prevalence of diabetes compared to a low-income and low educational level group.…”
Section: Characterizing the Chilean Health Care System: Consequences Of A Neoliberal Dictatorshipmentioning
confidence: 99%
“…High-income groups with high educational levels had a significantly lower prevalence of diabetes compared to a low-income and low educational level group. What explained the difference of prevalence in both groups was the average distance to their health centers: the low-income group’s distance to their health provider was almost double the distance of the high-income group ( Crespo et al, 2020 ).…”
Section: Characterizing the Chilean Health Care System: Consequences Of A Neoliberal Dictatorshipmentioning
confidence: 99%